Sesame seedlings cv. BRS Seda under saline water application - Cordão, Mailson Araujo; Sobrinho, Thiago Galvão; Andrade, Kyonelly Queila Duarte Brito; Tavares, Austro José Faustino; Nascimento, Ronaldo do (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
Sesame is an important oil and food crop, well adapted to semi-arid conditions, where a salinity problem or problem is common. Thus, the objective of this study was to evaluate the germination and growth of sesame seedlings submitted to salt stress. The treatments were arranged in a completely randomized design, applying five treatments, with the levels of salts corresponding to the electrical conductivities of the water (0.6; 1.2; 1.8; 2.4 and 3.0 dS m-1) in the BRS Seda sesame cultivar, distributed in four replications, totaling 20 experimental units. The variables analyzed were the percentage, the first count, the speed index, average germination time, and seedling growth variables: total seedling length, hypocotyl, primary root, vigor and total fresh mass of the area and primary root. The results obtained show that the increase in salinity in the water causes a reduction in the germination and in the initial growth of the sesame seedlings. It is not recommended to use water with salt concentrations from 1.2 dS m-1 in the establishment of the BRS Seda cultivar.